Work till old age: an analysis of self-employment’s impact on depression among the older adults in China - He, Li; Zhao, Jinxu; Li, Man; Song, Zhiyong; Ma, Yanling; Yang, Zhixiong (Frontiers in Psychiatry, 2024)
Background: Depression is a significant risk factor affecting the mental health of older adults. In the context of accelerated population aging and the policy of "delayed retirement," self-employment has become an important alternative for older adults. Thus, studying the difference in depression levels between self-employed older adults and retirees, along with the mechanisms behind these differences, has emerged as a crucial theoretical and practical issue.Methods: This research, based on panel data from the China Health and Retirement Longitudinal Study for the years 2011, 2013, 2015, and 2018, employed fixed-effect, instrumental variable, mediation models to analyze the difference in depression levels between self-employed older adults and retirees, as well as the mediating mechanisms involved.The findings indicate that self-employed older adults have lower levels of depression than retirees. The results of the mediating mechanism analysis suggest that self-employment can indirectly lower the depression levels of older adults by frequent social participation and greater life satisfaction. However, heterogeneity analysis revealed significant urban-rural differences and different types of self-employment in the impact of self-employment on the depression levels of older adults.The results of this study are of great significance for enhancing the mental health of older adults and provide empirical support for China and other developing countries in formulating more effective aging policies and building a more beneficial aging society.